Measuring physical load in soccer: Strengths and limitations of 3 different methods - Fischer-Sonderegger, K.; Taube, W.; Rumo, M.; Tschopp, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the strengths and limitations of different indicators to measure physical load. Furthermore, indicators were evaluated for discrimination between performance levels and playing positions. Methods: Ninety positional match files from 70 elite players and 91 match files from 69 subelite players were collected during 14 official under-18 matches using a local position measurement system. Indicators are calculated from speed, absolute acceleration (acc-abs), or percentage acceleration (acc-%). The acc-% describes the level of acceleration depending on the maximal voluntary acceleration (amax) for each initial running speed. Effect sizes (ES) were used to determine discriminative ability. Results: The number of high accelerations largely depended on the method (absolute threshold [>3 m·s-2 and >4 m·s-2] 120 and 59 efforts; high percentage threshold [>75% amax] 84 efforts). Only a small number of highly accelerated efforts reached speeds considered high-speed running (>19.8 km/h: 32.6%). More high acc-% exists from initial running speed >2 m/s (23.0) compared with acc-abs (>3 m·s-2 14.4, >4 m·s-2 5.9). Elite players achieve higher values in most performance indicators, with ES being highest for the number of high acc-% (ES = 0.91) and high acc-abs (>3 m·s-2 ES = 0.86, >4 m·s-2 ES = 0.87), as well as for covered distance in jogging (ES = 0.94). Conclusions: Estimated physical load, discriminative ability of physical indicators, and positional requirements largely depend on the applied method. A combination of speed-based and acc-% methods is recommended to get a comprehensive view.